ON LACUNARY STATISTICAL CONVERGENCE OF ORDER ? - Sengul, Hacer; Et, Mikail (Springer, 2014)
In this article, we introduce the concept of lacunary statistical convergence of order alpha of real number sequences and give some inclusion relations between the sets of lacunary statistical convergence of order alpha and strong N-theta(alpha) (p)-summability. Furthermore, some relations between the spaces N-theta(alpha) (p) and S-theta(alpha) are examined.
Keywords: Statistical convergence; lacunary sequence; Cesaro summability